Early assessment of pediatric oral status at national guard (NG)-cross sectional study - Maha Sami Eid; Mawadda Adel Alsairafi; Maysa Baharoon; Nouf Alshaaby; Enas Hawsawy; Huda A. Althbiti; Mohamed S. Alghamdi; Nasser Alhagan; Ola Balkhair; Ayman Nooh; Raniah Abdullateef Ba-Akdah (Saudi Dental Journal)
Introduction: According to the American Academy of Pediatric Dentistry, it is recommended that pediatric dental home begins before 12 months of age. Studies reported the prevalence of early childhood caries among preschool children in Saudi Arabia ranging from 85% to 96% However there was lack of studies reporting the prevalence of caries among infant/toddlers. In Riyadh city the incidence of dental trauma among children (6 months to 4 years) was recorded 12% and 48% and oral lesion was 10.26%. Aim: Assessment of oral health status for infants/toddlers between 6 months and 3 years old to determine frequency of dental caries, oral hygiene, dental trauma, oral lesion, and relate it to the caregiver oral care practice. Material & methods: Ethical approval was obtained from KAIMRC at KAMC-Jed. A collaboration between the Dental Department and Family Medicine Department at Iskan (PHC) Center in Jeddah was done at 2015/2016 to examine infant/toddlers oral health status at the well-baby clinic. This cross-sectional study is using the previously collected data in this first dental preventive program. The sample was 151 infant/toddlers. The chart included interview-based questionnaire which was answered by the caregiver during the visit. Results: The frequency of dental caries was9% with sever early childhood caries mostly affecting upper central incisors. This indicated the importance to establish early preventive dental care within well-baby clinic. The plaque was accumulated mostly on posterior teeth. The frequency of trauma was very low and no reported oral lesion. Conclusions: This study Indicated the urgent need to reach infant/toddlers within well-baby clinic to enhance early oral care and to preventive caries.